Hepcidin levels in diabetes mellitus and polycystic ovary syndrome. Issue 12 (19th August 2013) - Sam, A. H.; Busbridge, M.; Amin, A.; Webber, L.; White, D.; Franks, S.; Martin, N. M.; Sleeth, M.; Ismail, N. A.; Daud, N. Mat; Papamargaritis, D.; Le, C. W.; et al.
Abstract Aim Increased body iron is associated with insulin resistance. Hepcidin is the key hormone that negatively regulates iron homeostasis. We hypothesized that individuals with insulin resistance have inadequate hepcidin levels for their iron load. Methods Serum concentrations of the active form of hepcidin (hepcidin‐25) and hepcidin:ferritin ratio were evaluated in participants with Type 2 diabetes (n = 33, control subjects matched for age, gender and BMI, n = 33) and participants with polycystic ovary syndrome (n = 27, control subjects matched for age and BMI, n = 16). To investigate whether any changes observed were associated with insulin resistance rather than insulin deficiency or hyperglycaemia per se, the same measurements were made in participants with Type 1 diabetes (n = 28, control subjects matched for age, gender and BMI, n = 30). Finally, the relationship between homeostasis model assessment of insulin resistance and serum hepcidin:ferritin ratio was explored in overweight or obese participants without diabetes (n = 16). Results Participants with Type 2 diabetes had significantly lower hepcidin and hepcidin:ferritin ratio than control subjects (P < 0.05 and P < 0.01, respectively). Participants with polycystic ovary syndrome had a significantly lower hepcidin:ferritin ratio than control subjects (P < 0.05). There was no significant difference in hepcidin or hepcidin:ferritin ratio between participants with Type 1 diabetes and control subjects (P = 0.88 and P = 0.94). Serum hepcidin:ferritin ratio inversely correlated with homeostasis model assessment of insulin resistance (r = –0.59, P < 0.05). Conclusion Insulin resistance, but not insulin deficiency or hyperglycaemia per se, is associated with inadequate hepcidin levels. Reduced hepcidin concentrations may cause increased body iron stores in insulin‐resistant states.